L’histoire aux prises avec les mémoires. L’exemple du musée avorté de Montpellier sur l’histoire de la France et de l’Algérie - Jean-Robert Henry (L’Année du Maghreb)
Various attempts have recently been undertaken to put the historical knowledge produced on Franco-Maghreb relations within the reach of the general public, especially students at school. The Museum of France and Algeria History in Montpellier was one of the most ambitious. Rephrasing a project initially focused on the memory expectations of the French in Algeria, he mobilized dozens of professionals of heritage and French and Algerian researchers to try to propose a common path in the history of the two countries. It was less a question of confronting multiple and divergent memories than of inviting the bearers of these to submit to a duty of history in order to enter into a dialogue.But in June 2014, the new mayor of Montpellier suddenly decided to stop the museum project, under pressure of Algerianist associations particularly. For several months, this decision provoked a very lively and wide public debate. The paper, written by the former chairman of the museum’s scientific committee, recalls the genesis and development of the project and questions the reasons both structural and short-term, local and national, which have weighed on its abandonment. Conversely, the strong reaction of academic and cultural circles also led to validating the interest of the undertaking, as evidenced by the survival of certain aspects of the project and the attempt of the Head of State to relaunch it in 2016. The lesson that remains from this experience is that the crossed history of France and the Maghreb is more than ever necessary, but can hardly find a place in memory politics with ambiguous objectives.